Asymmetric crying facies – its meaning in the differential diagnosis of congenital developmental abnormalities - Michalska, Agata; Połatyńska, Katarzyna; Kępczyński, Łukasz; Szczukocki, Maciej (Medical Studies/Studia Medyczne, 2019)
The symmetry of a newborn baby’s head and face, including the symmetry of a palpebral fissure, auricles, nose, and the movement of eyelids and mouth, is evaluated during a newborn baby’s overall examination. Asymmetric crying facies (ACF) is a congenital disorder resulting from unilateral hypoplasia, or from agenesis of the depressor anguli oris muscle or rarely of the depressor of the edge of the mouth and depressor of labii inferioris. The ACF incidence rate oscillates at about 0.3%, with the dominance of a left-handed disorder. Isolated ACF is treated as a cosmetic defect, although it can accompany a wide range of developmental disorders, the most common of which is congenital facial nerve palsy. In every case, a profound morphological and anatomical evaluation should be executed because, if necessary, the molecular analysis should be widened.